Regulation of Virulence in Staphylococcus aureus: Molecular Mechanisms and Remaining Puzzles - Wang, Boyuan; Muir, Tom W. (Cell chemical biology, 2016)
The agr locus encodes a quorum-sensing (QS) circuit required for the virulence of a spectrum of Gram-positive pathogens and is, therefore, regarded as an important target for the development of chemotherapeutics. In recent years, many of the biochemical events in the Staphylococcus aureus agr circuit have been reconstituted and subject to quantitative analysis in vitro. This work, in conjunction with structural studies on several key players in the signaling circuit, has furnished mechanistic insights into the regulation and evolution of the agr QS system. Here, we review this progress and discuss the remaining open questions in the area. We also highlight advances in the discovery of small-molecule agr modulators and how the newly available biochemical and structural information might be leveraged for the design of next-generation therapeutics targeting the agr system. •Quorum sensing encoded by the agr locus regulates virulence in Staphylococcus aureus•In vitro reconstitution yields new mechanistic insights into the quorum sensing•A hypothetical evolution trajectory for the emergence of agr variants is proposed•Recent findings provide new opportunities to the development of agr modulators Many processes, like virulence, in Staphylococcus aureus are under control of a quorum sensing system, the accessory gene regulator (agr) locus. Wang and Muir review the most recent insights into how agr locus functions and what some of the ways to develop small molecules to modulate it are.